Isocratic high-performance liquid chromatography (HPLC) for simultaneous quantification of curcumin and piperine in a microparticle formulation containing Curcuma longa and Piper nigrum. Issue 3 (March 2021) - Setyaningsih, Dewi; Santoso, Yosua Agung; Hartini, Yustina Sri; Murti, Yosi Bayu; Hinrichs, Wouter L.J.; Patramurti, Christine
Abstract: Poor bioavailability has been reported as a major challenge in the development of curcumin as a pharmaceutical agent. However, co-administration of curcumin with piperine has been shown to improve curcumin bioavailability. Therefore, to assure product control quality, an analytical method needs to be developed for the determination of curcumin and piperine content in a dosage form formulation. The objective of this study was to develop a simple isocratic reversed-phase HPLC (RP-HPLC) method to simultaneously quantify curcumin and piperine content in solid dispersion based microparticle formulation containing Curcuma longa and Piper nigrum extracts. The method was validated according to the International Council for Harmonization (ICH) guideline. Chromatographic separation of three curcuminoids and piperine could be achieved using acetonitrile-methanol-water of 65:5:35 %, at a flow rate of 1 mL/min and a wavelength of 353 nm for detection. Resolution (Rs) of 3.57 and 1.68 for piperine and curcumin, respectively, a theoretical plate number (N) > 8000 and a tailing factor (T) < 1.5 indicate a satisfactory separation of the compounds. The calibration curve was linear from 1.25-15 μg/mL and 2.5–30 μg/mL for piperine and curcumin, respectively, with the correlation coefficient of >0.999. The intra-day/inter-day accuracy and precision demonstrated a recovery of 99.54–101.50%/99.38–99.89% and 100.78–102.51%/101.15–102.47% with a Relative Standard Deviation (RSD) of 0.53–0.95%/0.13–1.44 % and 0.28–1.62%/0.46–1.14% for piperine/curcumin. The limit of detection (LOD) were 0.27 and 0.42 μg/mL, for piperine and curcumin, which reveals an adequate sensitivity. A solid dispersion based microparticle formulation containing C. longa and P. nigrum extracts confirmed the validity of the developed method as a recovery of 91.14% and 99.14% for piperine and curcumin, respectively. In conclusion, all the tested parameters confirm the precision, accuracy, and reliability of the method for the simultaneous analysis of curcumin and piperine within a microparticle formulation containing C. longa and P. nigrum extracts. Abstract : Curcumin; Piperine; Extract; Solid dispersion; Reverse-phase; Validation; Optimization.